Description of a new species of Myrmecotypus (Araneae: Corinnidae: Castianeirinae), the first of its genus known from Paraguay, with an updated key to species - Pett, Brogan L. (Zootaxa, 2021)
The castianeirine spider genus Myrmecotypus O. Pickard-Cambridge, 1894 is reported from Paraguay for the first time, with the description of a new species, Myrmecotypus mboitui sp. nov. (♂♀) from the Ñeembucú Wetlands Complex of south-western Paraguay. The species belongs to a small group of Myrmecotypus with elongated and constricted abdomens. Illustrations of the diagnostic characters of the new species are provided. An updated key to the species of Myrmecotypus is presented.